Extending of Technology Acceptance Model in Using Online Health Applications in The Covid-19 Pandemic Era - Setyawan, Didik; Ashari, Muhammad Zul; Yulandari, Ariefah (Future Science / FSH-PH Publications, 2021)
The Covid-19 pandemic has changed behavior of the people in getting health services that switch to online ones. The study examines the extending of the Technology Acceptance Model (TAM) in using health applications. TAM is no longer relevant to be applied on the specific application studies. The expansion that carried out adds to the variables of social influence, feelings of anxiety, and availability of services in developing attitudes to influence behavioral intentions. Data collected using online questionnaires for users of the Halodoc application as many as 200 respondents. The results of hypothesis testing using the Structural Equation Modeling analysis with the AMOS method show that attitudes are the determinants in forming behavioral intentions which are influenced by perception of usefulness, ease of perception, social influence, and service availability, but not from the feelings of anxiety. These results indicate that individuals perceive Halodoc as providing benefits, easy to use, influencing environment, and well-available services. Therefore it can ignore the anxiety in using the Halodoc application during the Covid 19 pandemic to get health services.